Tuberous sclerosis complex (TSC) gene involvement in sporadic tumours. (1st June 2003) - Knowles, M.A.; Hornigold, N.; Pitt, E.
Abstract : In tuberous sclerosis patients, inactivation of the tuberous sclerosis complex tumour-suppressor genes TSC1 and TSC2 contributes to the development of a wide range of hamartomatous lesions. These patients do not, however, show an increased risk of the common adult solid cancers. Recent evidence that the TSC genes play a role in the phosphoinositide 3-kinase pathway, a pathway whose dysregulation is implicated in a wide range of human malignancies, raises the possibility that their inactivation could contribute to the development of some sporadic cancers. To date the only evidence for this comes from the finding of mutations of TSC1 in bladder cancer. The mutation spectrum of TSC1 in bladder cancer and functional evidence from TSC1 -gene-replacement studies in bladder tumour cells will be presented. The literature on genetic changes in several other sporadic epithelial cancers reveals relatively common deletions in the region of the TSC genes. In ovarian and gall bladder carcinoma and non-small-cell carcinoma of the lung, deletions in both 16p13 and 9q34 are found at significant frequency. Mutation analyses in such tumours are now merited.